PERFORMANCE OF POLICE PERSONNEL AT JAMBI POLICE (TRANSFORMATIONAL LEADERSHIP STYLE PERSPECTIVE AND WORK MOTIVATION) - Steven Kurniawan; Sry Rosita; Tona Aurora Lubis (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2023)
The purpose of this study was to describe the transformational leadership style through work motivation on the performance of police officers, to determine and analyze the transformational leadership style that has a significant influence on the performance of police officers, to determine and analyze work motivation has a significant influence on the performance of police officers, To find out and analyze the transformational leadership style has a significant influence on the work motivation of Police Members and to find out and analyze the transformational leadership style through work motivation has an influence on the performance of Police Members. The analytical tool used is PLS analysis. The results of the research that transformational leadership style has no significant effect on the performance of police officers at the Jambi Police. This means that the transformational leadership style does not have a direct influence on the performance of members of the Police at the Jambi Police. Work motivation has a positive and significant effect on the Performance of Police Members at the Jambi Police. This means that if work motivation increases, the performance of police officers will increase. The transformational leadership style has a significant effect on the work motivation of Police Members at the Jambi Police. This means that if the transformational leadership style increases, work motivation will increase. Transformational leadership style has a positive and significant effect on the performance of Police Members at the Jambi Police through work motivation.